LncRNA LOC105378097 inhibits cardiac mitophagy in natural ageing mice. Issue 6 (27th June 2022) - Liu, Xin; Bai, Xue; Liu, Heng; Hong, Yang; Cui, Hao; Wang, Lei; Xu, Wanqing; Zhao, Limin; Li, Xiaohan; Li, Huimin; Li, Xia; Chen, Hui; et al.
Abstract: Background: The development of heart ageing is the main cause of chronic disability, disease and death in the elderly. Ample evidence has established a pivotal role for significantly reduced mitophagy in the ageing heart. However, the underlying mechanisms of mitophagy deficiency in ageing heart are little known. The present study aimed to explore the underlying mechanisms of lncRNA LOC105378097 (Senescence‐Mitophagy Associated LncRNA, lncR‐SMAL) actions on mitophagy in the setting of heart ageing. Methods: The expression of lncR‐SMAL was measured in serum from different ages of human and heart from different ages of mice through a quantitative real‐time polymerase chain reaction. The effects of lncR‐SMAL on heart function of mice were assessed by echocardiography and pressure‐volume measurements system. Cardiac senescence was evaluated by hematoxylin‐eosin staining, senescence‐associated β‐galactosidase staining, flow cytometry and western blot analysis of expression of ageing related markes p53 and p21. Cardiomyocyte mitophagy was assessed by western blot, mRFP‐GFP‐LC3 adenovirus particles transfection and mito‐Keima staining. Interaction between lncR‐SMAL and Parkin was validated through molecular docking, RNA immunoprecipitation (RIP) and RNA pull‐down assay. Ubiquitination assay was performed to explore the molecular mechanism of Parkin inhibition. The effects of lncR‐SMAL on mitochondrial function were investigated through electron microscopic examination, JC‐1 staining and oxygen consumption rates analysis. Results: The heart‐enriched lncR‐SMAL reached the expression crest in the serum of human at an age of 60. Exogenously overexpression of lncRNA SMAL deteriorated cardiac function exactly as natural ageing and inhibited the associated cardiomyocytes mitophagy by depressing Parkin protein level. Improved heart ageing and mitophagy caused by Parkin overexpression were reversed by lncR‐SMAL in mice. In contrast, the loss of lncR‐SMAL in AC16 cells induced the upregulation of Parkin protein and ameliorated mitophagy and mitochondrial dysfunction, resulting in alleviated cardiac senescence. Besides, we found the interaction between lncR‐SMAL and Parkin protein through computational docking analysis, pull‐down and RIP assay. This would contribute to the promotive effect of lncR‐SMAL on Parkin ubiquitination and decrease Parkin protein stability. Conclusions: The present study for the first time demonstrates a heart‐enriched lncRNA, SMAL, that inhibits the mitophagy of cardiomyocytes via the downregulation of Parkin protein, which further contributes to heart ageing and cardiac dysfunction in natural ageing mice. Abstract : (1) The heart‐enriched lncR‐SMAL is robustly increased in its level in serum samples of human subjects over 60‐year old relative to young controls, and in both nucleus and cytoplasm of senescent cardiomyocytes. (2) Artificial overexpression of lncR‐SMAL induces cardiac senescence by inhibiting Parkin‐mediated mitophagy. Knockdown of endogenous lncR‐SMAL in cardiomyocytes partially abrogated cell senescence. (3) LncR‐SMAL interacts with Parkin protein and promotes ubiquitin‐proteasome degradation of Parkin in senescent cardiomyocytes.